Mengamankan RFID di Jaringan IoT dengan Pendekatan Kriptografi AES dan ECDH Ringan - Robby Kurniawan Harahap; Alief Vickry Thaha Maulidzart; Antonius Irianto Sukowati; Dyah Nur’ainingsih; Widyastuti; Desy Kristyawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2024)
Radio frequency identification (RFID) technology integrated into the Internet of things (IoT) networks often poses security and privacy concerns due to its attack vulnerability. This research proposed a lightweight cryptographic model tailored for implementation in resource-constrained environments. The objective is to address security challenges while accommodating limited memory, power, and size requirements. A combined modified 126-bit Advanced Encryption Standard (AES) algorithm with a 256-bit elliptic curve Diffie-Hellman (ECDH) cryptographic key was utilized to develop lightweight cryptography for securing RFID data. The implementation used the Python programming language in Jupyter Notebook, with RFID operating at 13.56 Mhz. The methodology involved retrieving RFID data through additional programs and equalizing ECDH keys for encryption and decryption. Encryption and decryption testing demonstrated a high success rate, achieving an accuracy of 99.9%. The first encryption attempt required 85.125 ms, with the second attempt completed faster at 65.95 ms, showcasing improved efficiency. File encryption sizes averaged 29.875 bytes for the initial attempt and 30.1 bytes for the subsequent one. This research was limited to algorithm evaluation and had not been implemented in hardware. However, the proposed hybrid cryptography offers significant benefits for maintaining the confidentiality of RFID data within IoT environments. Rapid, efficient, and compact encryption of unique identifier (UID) data ensures enhanced security, thereby addressing critical concerns associated with RFID-enabled IoT networks.